The role of self-regulation in environmental behavior change - Kristian Steensen Nielsen (Copenhagen Business School (CBS), 2019)
A rapid and global transition is needed to prevent catastrophic climate change. This transition requires, amongst other, profound behavioral changes to reduce the emission of greenhouse gasses and other environmental impacts. Within psychology, researchers have studied the psychological constructs that predict the performance of environmentally friendly behaviors and how utilizing and manipulating these constructs can bring about behavioral changes. Limited research has, however, studied the dynamics of the behavior-change process itself to uncover the processes that determine the success or failure of environmental behavior change. To address this research gap, the dissertation investigates the role of self-regulation in behavior change that is voluntarily undertaken to limit environmental impacts. Studying self-regulation-the processes that enables humans to guide their behavior over time and builds on the capacity to influence, modify, and control their own behavior-can help identify key self-regulatory problems and strategies to overcome them.
hdl:10398/9749
Keywords: 650; Umweltschutz; Selbstverpflichtung